Levamisole: A Positive Allosteric Modulator for the α3β4 Nicotinic Acetylcholine Receptors Prevents Weight Gain in the CD-1 Mice on a High Fat Diet - Lewis, Jeanne A. (Curr Pharm Des, 2017)
Neuronal nicotinic acetylcholine receptors (nAChRs) regulate the function of multiple neurotransmitter pathways throughout the central nervous system. This includes nAChRs found on the proopiomelanocortin neurons in the hypothalamus. Activation of these nAChRs by nicotine causes a decrease in the consumption of food in rodents. This study tested the effect of subtype selective allosteric modulators for nAChRs on the body weight of CD-1 mice. Levamisole, an allosteric modulator for the α3β4 subtype of nAChRs, prevented weight gain in mice that were fed a high fat diet. PNU-120596 and desformylflustrabromine were observed to be selective PAMs for the α7 and α4β2 nAChR, respectively. Both of these compounds failed to prevent weight gain in the CD-1 mice. These results suggest that the modulation of hypothalamic α3β4 nAChRs is an important factor in regulating food intake, and the PAMs for these receptors need further investigation as potential therapeutic agents for controlling weight gain.